2020
DOI: 10.1108/jsm-05-2019-0209
|View full text |Cite
|
Sign up to set email alerts
|

The value disruption of uncivil other-customers during online service recovery

Abstract: Purpose Customer complaints and service recovery via virtual customer service channels (VCSCs) present unique recovery situations unlike those commonly found in traditional complaint handling channels. Some of these distinct challenges include the presence of multiple customers during a recovery, which creates the possibility for uncivil customer-to-customer (C2C) exchanges to harm a complainant’s experience. To this end, this paper aims to explore customer- and firm-level aspects as they relate to social medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 79 publications
0
20
0
4
Order By: Relevance
“…Luxury brands face the challenge of maintaining their brand integrity in the era of ubiquitous consumer-generated content; positive reviews on social media can have negative impacts on purchase intentions as they may encourage social comparison and trigger feelings of malicious envy (Feng et al, 2021), and negative word of mouth can be perilous for brand image (Gensler et al, 2013). Negative interactions such as consumer bullying or abusing other consumers on brands' social media pages may undermine the brands' value (Bacile et al, 2018(Bacile et al, , 2020. Future researchers should consider the duality of social media and explore how social media interaction can have negative effects on luxury brands and consumers.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Luxury brands face the challenge of maintaining their brand integrity in the era of ubiquitous consumer-generated content; positive reviews on social media can have negative impacts on purchase intentions as they may encourage social comparison and trigger feelings of malicious envy (Feng et al, 2021), and negative word of mouth can be perilous for brand image (Gensler et al, 2013). Negative interactions such as consumer bullying or abusing other consumers on brands' social media pages may undermine the brands' value (Bacile et al, 2018(Bacile et al, , 2020. Future researchers should consider the duality of social media and explore how social media interaction can have negative effects on luxury brands and consumers.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…But this effect can be offset by a prompt response on the part of the firm to customer online incivility. Bacile et al (2020) noticed that the presence of other customers can negatively influence a focal complainant's perceptions of justice and subsequent experiential value, with this effect also depending on the brand's promptness in responding and on the complainant's personal characteristics. When other customers interject in the complainant–service provider exchange on social media, Bacile (2020) concluded that online incivility that is perceived to be unfair diminishes customer perceptions of the service climate, especially when the service provider fails to address the incivility.…”
Section: Brand Activism and Uncivil Reactions On Social Mediamentioning
confidence: 99%
“…Second, our study contributes to the marketing domain with knowledge related to online incivility. Most of the existing research in this area features customer-to-customer online incivility (Bacile 2020; Bacile et al 2020). Previous research in service recovery and brand response has investigated how brands should respond to consumer complaints on social media (e.g., in an accommodative or defensive way), considering the role of observers of the communication between dissenters and brands (Johnen and Schnittka 2019).…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%
See 2 more Smart Citations